MENAKAR TANGGUNG JAWAB NEGARA DALAM PERLINDUNGAN KONSUMEN PRODUK IMPOR HALAL: ANALISIS ATAS NEGOSIASI DAGANG INDONESIA – AMERIKA SERIKAT - Sakti, Muthia; Priambodo, Rio; Afifullah, Muhamad (International Journal Mathla’ul Anwar of Halal Issues, 2026)
This study aims to analyze the state’s responsibility in protecting consumers of imported halal products and to examine the implications of Indonesia–United States trade negotiations for the implementation of the Halal Product Assurance Law (UU JPH) within a standards-based global trade landscape. It employs a normative legal research method using statutory, conceptual, and comparative approaches. The analysis evaluates national regulations alongside the principles of non-discrimination and equivalence under the WTO regime to determine the limits of trade compromise. The findings indicate that mandatory halal certification constitutes a constitutional mandate that cannot be substantively negotiated. Recognition of foreign halal certificates may only be granted through a strict, transparent, and proportional equivalence assessment to ensure an equivalent level of protection for Muslim consumers. Trade negotiations do not eliminate regulatory sovereignty; rather, they require the design of recognition mechanisms that preserve the integrity of the national halal assurance system and remain consistent with international trade law.